The Rise of Religious Fundamentalism in the Post War Era of Sri Lanka: A Probable Christian Response - Siyanstan Jenis, A. (University of jaffna, 2024)
“Have the religions lost their nature and purpose in Sri Lanka?’’ The prolonged civil war, attacks on religious worshiping places and the hatred attitude and rivalry among the religions make one to ask this question frequently. The end of civil war brought in a shift in the perspective of Sri Lankan people from ethnicity to religious fundamentalism which has never been experienced as such in the history of Sri Lanka. The fact is that Christianity has fallen a prey to this religious fundamentalism. The Hindu fundamentalist groups join hands with Buddhist fundamentalists with the concept that both Hinduism and Buddhism are ancient religions of Sri Lanka. This concept creates suspicion and fear towards Christians and any effort taken by Christians are viewed as threats. In addition, the Easter attack, carried by Islamic fundamentalist group is another challenge encountered by Christians. Considering the ground reality, there lies big responsibility in front of all Christians in Sri Lanka to engage in dialogue and thus to ensure religious harmony and being tolerant. The purpose of dialogue is growth and change. It must lead to a mutual growth in understanding of truth on the part of dialogue partners. The life of Jesus shows the way to encounter such a situation. He embraced everyone and initiated conversations not conversion spontaneously which made the people who listened, to have a change in their lives. Christians must analyze and study the roots for this fundamentalistic acts and work on it. By our acts of love and service we must eradicate misconceptions and fear that were basically created in the past. Imparting the knowledge has been a great endeavour of Christians in Sri Lanka. We can make use of this as a common platform to guide people to promote religious harmony and righteousness. Therefore, the rise of religious fundamentalism in Sri Lanka is not the biggest challenge compared to the experience of coexistence of all religious people but at the same time we, Christians cannot be indifferent to it.
Keywords: Fundamentalism; Interreligious dialogue; Harmony, mutual; Religious harmony